Na Nowy Rok przybywa dnia na kurzy krok, a na Trzy Króle na owczy skok: Nazwy miar wydłużającego się dnia utrwalone w przysłowiach polskich - Popławski, Emil (LingVaria, 2024)
NAMES OF MEASURES OF THE LENGTHENING DAY RECORDED IN POLISH PROVERBSThe article concerns the characteristic names of time measures that appear in the proverb calendar in Polish and other languages. These include: barani/kurzy owczy/wilczy/zajęczy skok; kurzy krok; kurze postąpienie/stąpienie; kurza stopa/stopka; kura pianie zapianie oraz wołowe wyleżenie/zależenie. These measures refer to the slightly lengthening day after the winter solstice (22 December). They indicate fairly short stretches of time, between a few and several minutes, which are almost imperceptible to the average person. These names are motivated by observations of the behaviour of farmed and wild animals. The most common of these references to the hen (Polish: kura or kur) have roots in ancient beliefs.